Peningkatan Pemahaman Konsep Matematis Melalui Teams Games Tournament Berbantuan Media TAPIN Pada Siswa Sekolah Dasar - Nurul Aini; Lovika Ardana Riswari; Wawan Shokib Rondli (Universitas Khairun, 2026)
Abstract : This study was motivated by the low level of mathematical conceptual understanding among elementary school students regarding whole numbers, a result of instruction that had not optimally incorporated collaborative activities and concrete media. The study aimed to describe the improvement in students' mathematical conceptual understanding through the Teams Games Tournament (TGT) model supported by TAPIN media. It employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, involving 16 students from class VA at SDN Slungkep 03. Data were collected through observation, interviews, documentation, and tests, and subsequently analyzed both quantitatively and qualitatively. The research indicates that students' learning proficiency improved, rising from an initial 31% to 56% in Cycle I and 88% in Cycle II. The findings demonstrate that the TGT model supported by TAPIN media enhances students' mathematical conceptual understanding through collaborative, interactive learning that utilizes concrete media. It can be concluded that the Teams Games Tournament (TGT) model supported by TAPIN media is effective in improving elementary school students' mathematical conceptual understanding of whole numbers. Keywords : TAPIN Media; mathematical conceptual understanding; Teams Games Tournament